“A Fine, Hardy, Good-Looking Race of People”: Travel Writers, Tourism Promoters, and the Highland Scots Identity on Cape Breton Island, 1829-1920 - Little, J. (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2015)
Based on an examination of travel narratives and promotional publications, this article suggests that the romantic image of Cape Breton Island as a bastion of traditional Highland culture can be traced to the 1870s with the dawning of American antimodernism. American publications continued to feature somewhat condescending portraits of a people “far removed from the modern age,” but they also expressed admiration for a way of life that was tied to tradition and close to nature. This longing, followed by the re-emergence of the traditional image of the heroic Highland warrior, occurred well before Premier Angus L. Macdonald began his “tartanizing” campaign for the province as a whole in the 1930s.